Global Anticoagulant Registry in the Field – Venous Thromboembolism (GARFIELD-VTE) - Weitz, Jeffrey I.; Haas, Sylvia; Ageno, Walter; Angchaisuksiri, Pantep; Bounameaux, Henri; Nielsen, Joern Dalsgaard; Goldhaber, Samuel Z.; Goto, Shinya; Kayani, Gloria; Mantovani, Lorenzo; Prandoni, Paolo; Schellong, Sebastian; Turpie, Alexander G. G.; Kakkar, Ajay K. (Thrombosis and Haemostasis, 2016)
Venous thromboembolism (VTE) is a common disorder associated with significant rates of morbidity and mortality. VTE management aims to reduce mortality, the risks of recurrence, and long-term complications. VTE treatment is evolving with the introduction of non-vitamin K antagonist anticoagulants (NOACs). The Global Anticoagulant Registry in the FIELD – Venous Thromboembolism (GARFIELD-VTE) is a prospective, multicentre, observational study that will enrol 10,000 patients treated for acute VTE from ∼500 sites in 28 countries. Identified sites reflect the diversity of care settings, including hospital and outpatient settings. Patients will be managed according to local practices and followed for at least three years. The primary objective is to determine the extent to which VTE treatment varies in the real-world setting and to assess the impact of such variability on clinical and economic outcomes. Evolving patterns of care will be captured using two sequential cohorts. The GARFIELD-VTE registry will provide insights into the evolving global treatment patterns for VTE, both deep-vein thrombosis and pulmonary embolism. By enrolling patients from diverse care settings, the registry will provide information on adherence to national and international guidelines, identify good practice as well as treatment deficiencies, and relate patient outcomes to clinical management. The incidence of death, recurrent VTE, bleeding, post-thrombotic syndrome and chronic thromboembolic pulmonary hypertension will be documented. By capturing information during and after anticoagulation treatment, the registry will not only define aspects of the natural history of VTE, but also its economic and societal impact at a regional and global level.
Keywords: Registry; venous thromboembolism; deep-vein thrombosis; pulmonary embolism; anticoagulation; thrombolysis